Unilateral involuntary movements of the limbs with caudate nucleus restricted diffusion on magnetic resonance imaging: A case report - Lan Deng; Bing-Hu Li (Journal of International Medical Research)
Anti-leucine-rich glioma-inactivated-1 (LGI1) autoimmune encephalitis is one of the most prevalent forms of autoantibody-associated limbic encephalitis. Brain magnetic resonance imaging of patients with anti-LGI1 encephalitis often presents as fluid-attenuated inversion recovery hyperintensities of the medial temporal lobe. We report the case of a man in his early 60s who suddenly experienced involuntary movement of the right limbs. Brain magnetic resonance imaging revealed normal T1 signal and T2 hyperintensity in the left caudate nucleus, with corresponding fluid-attenuated inversion recovery hyperintensity, diffusion-weighted imaging hyperintensity, and apparent diffusion coefficient hypointensity. The patient was ultimately diagnosed with anti-LGI1 autoimmune encephalitis. For patients with unilateral involuntary movement accompanied by restricted diffusion in the basal ganglia region, anti-LGI1 encephalitis should be considered.